Extended endoscopic endonasal approach for resecting anterior intrinsic third ventricular craniopharyngioma - Zhou, Yuefei; Wei, Jialiang; Jin, Tao; Hei, Yue; Jia, Pengfei; Lin, Jincai; Yang, Shuangwu; Jiang, Xiaofan; Liu, Weiping; Gao, Dakuan (Frontiers in Oncology, 2022)
Background: The surgical treatment of the extended endoscopic endonasal approach (EEEA) is a safe and effective treatment for suprasellar craniopharyngiomas. However, due to damage to the hypothalamus and third ventricle floor (TVF), EEEA is generally regarded as unsuitable in treating intrinsic third ventricle craniopharyngioma (ITVC) that is entirely within the third ventricle. Until now, there have been only a small number of reports using EEEA to treat TVC via a supra-infrachiasmatic approach. Given that the translamina terminalis (TLT) corridor was used in the transcranial subfrontal approach, EEEA via a suprachiasmatic approach may be feasible and practical to treat ITVC. In the current study, we accumulated experience applying the suprachiasmatic translamina terminalis (STLT) corridor for anterior treatment of ITVC. Methods: From March 2016 to December 2020, 14 patients with ITVC in our center were analyzed retrospectively. All patients underwent surgery by EEEA via an STLT corridor. The multilayer reconstruction technique was adopted to achieve skull base reconstruction. Data concerning the patient’s tumor resection, vision, hypophyseal hormone, and complications were collected. Results: Gross-total resection was achieved in 13 (92.8%) of14 patients, with achievement of near-total (90%) resection in the remaining 1 patient. Nine cases (64.3%) were papillary craniopharyngiomas, and the other 5 cases were adamantinomatous subtypes. Postoperatively, 3 patients with pituitary insufficiency received hormone replacement therapy. No permanent diabetes insipidus or hypothalamic obesity was found. All pairs showed significant improvement or stability in vision except 1 patient who encountered visual deterioration. No other neurological deficit occurred postoperatively. Observation results for the exudation of nasal tissue and the length of hospitalization were satisfactory. After a mean follow-up period of 26.2 months, tumor recurrence was not observed. Conclusion: TLT is a minimally invasive corridor used in EEEA for treating anterior ITVC without increasing risks of visual and hormonal deficits. The multilayered reconstruction technique we used is a safe and effective method for achieving watertight closure and avoiding cerebrospinal fluid leaks and infection. The endonasal approach via STLT provides a new, safe and efficacious operative strategy that should be considered a surgical alternative in treating ITVC.